PENGARUH JENIS PEKERJAAN DAN TINGKAT PENDIDIKAN TERHADAP PERCERAIAN DI PENGADILAN AGAMA SEMARANG TAHUN 2015 - Rokhmadi, Rokhmadi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2018)
This research tries to know the influence of work type and level of education to divorce in Religious Court of Semarang Year 2015. This type of research is field research that is quantitative and qualitative in nature. The quantitative approach, which is to find out the relationship and differences in the variables influence the type of work, and the level of education to the occurrence of divorce in the Semarang Religious Court in 2015. While the qualitative data approach is used as an analysis material from quantitative results. The result of first hypothesis in this research is accepted that society having background of work type non-state civil apparatus will tend to easier to divorce, while people with a background of the type of work as state civil apparatus servants tend to be better able to control themselves from divorce, because the variables not in the equation score 6.512 with a significance level of 0.011 smaller than 0.05 (0.011 <0.05). The second hypothesis is accepted that people with with elementary and secondary will tend to be easier to divorce, while those with higher education will tend to be better able to control themselves from divorce because the variables not in the equation score of 5,738 with significance level of 0.017 less than 0.05 (0.017 <0.05); and the third hypothesis is also accepted that people with background of non-state civil apparatus and elementary and secondary will tend to be easier to divorce, whereas people with background types of work as State civil apparatus and higher education will tend to be more able to control themselves from divorce, because the variables not in the equation scores are 10.861 with a significance level of 0.004 smaller than 0.05 (0.004 <0.05).